Cold War Revival: Neoconservatives and Historical Memory in the War on Terror - Noon, David Hoogland (American Studies, 2007)
Throughout the cold war, neoconservative intellectuals argued that the United States is an inherently virtuous nation engaged a permanent struggle against enemies at home as well as abroad. This essay addresses the ways that contemporary neoconservative voices have tried to revive the narrative of struggle, in part by claiming that the war on terror must be understood as a “present danger” that resembled the cold war. According to these commentators, a victorious strain of American foreign policy was born during the early years of the cold war. After three decades of setbacks and faltering national “will,” these principles were supposedly were reanimated by Ronald Reagan, who eventually carried the nation to triumph. By arguing that Americans are capable of restoring abandoned paths to victory, neoconservatives insist that the lessons of the cold war must be revived and applied to the struggle against radical Islam.